Bahay kubo Regal Entertainment Production ; a film by Joel C. Lamangang. - Lamangan, Joel.; Soriano, Maricel; Quizon, Eric.; Rivera, Marian; Magdayao, Shaina; Regal Entertainment Production ([Pasig City] Regal Entertainment Production, 2008)
When her mother Ida (Gloria Romero) comes home with an abandoned baby, Eden (Maricel Soriano) is at first outraged, but she becomes all the more caring with Lily (Marian Rivera). Seeing this as her new calling. Fate begins to drop more eggs in her maternal basket. She soon finds her bahay kubo swamped with orphans and with her new found love - Perry (Eric Quizon). But all is not as rosy as it seems, as the family moves away from their bahay kubo to a mansion in Manila, problems beset their growing house hold. Her husband Perry fueled by his ambitions, has unwillingly place his family in dishonor and debt.
DVD
Maricel Soriano, Eric Quizon, Marian Rivera, Shaina Magdayao.
Keywords: Drama--Feature.; Family; Feature films